Promiscuity in molecular mimics of the cysteine dioxygenase: effects of selenium in the substrate and cobalt as the central metal ion - Weißer, Kilian; Weber, Edgar T. K.; Velmurugan, Gunasekaran; Cula, Beatrice; Krause, Konstantin B.; Wolff, Siad; Mubarak, M. Qadri. E.; Comba, Peter; Visser, Sam P. de; Limberg, Christian (Angewandte Chemie. International edition, 2025)
Cysteine dioxygenase (CDO) catalyzes the conversion of cysteine with dioxygen to yield cysteine sulfinic acid, which lies at the branching point of cysteine catabolism. Despite many years of research there are still many questions related to its functioning. Thus, CDO is inactive with selenocysteine (Sec) or when the central iron ion is replaced by cobalt. In this context, we report here biomimetic CDO models with bound selenocysteamine substrate ligands, namely [TpMesFe(Se-CH2-CH2-NH2)] and [TpMes*Fe(Se-CH2-CH2-NH2)] (with TpMes = hydrotris(3-mesitylpyrazol-1-yl)borate, TpMes* = hydrobis((3-mesitylpyrazol-1-yl)(5-mesitylpyrazol-1-yl)borate) and in addition a cobalt-analogue [TpMesCo(Se-CH2-CH2-NH2)]. Upon treatment of the Fe/Se homologues with O2 - as in case of the parent cysteamine-bound complexes - the dioxygenation of the chalcogen atoms was observed. This suggests that the lack in reactivity of CDO-Sec toward O2 does not originate in the electronic situation but in the surrounding protein matrix. Subsequent DFT calculations indeed showed lower initial barriers for selenocysteamine than for cysteamine in support of the experimental work. The complex [TpMesCo(Se-CH2-CH2-NH2)], where Fe is formally replaced by Co, also reacts with dioxygen - more slowly but selectively - to give [TpMesCo(O2Se-CH2-CH2-NH2)]. Hence, this is an experimental observation of a dioxygenation with O2 mediated by a cobalt center in a molecular compound, which is so far without precedence.